E-026 Time and Pressure - Possible Reasons Behind Worse Outcomes For GETA Patients Undergoing Stroke Interventions. (26th July 2014) - Rai, A; Boo, S; Domico, J; Roberts, T; Carpenter, J
Abstract : Background: Several publications have shown poor outcomes for GETA patients undergoing endovascular stroke interventions. Our goal was to examine the factors directly related to GETA that may impact procedural outcomes. Our hypothesis being that GETA patients are sicker, the procedure may take longer and there may be fluctuations in blood pressure. Methodology: An IRB approved retrospective analysis was performed on patients that had undergone stroke interventions over the last 5-years and for whom anesthesia records were available. Blood pressure parameters and time intervals were recorded at multiple steps during a patient's progress from the ER to the ICU. Patient demographic information and comorbidities were also recorded, as was 90-day clinical outcome. Results: Out of 190 patients, GETA was administered in 108(56.8%) and non-GETA in 82(43.2%) patients. The mean age was 67.9(±16.2) years in the GETA and 67.1(±17) years in the non-GETA-group (p = 0.7). The mean NIHSS was 18.9(±8.7) in the GETA versus 13.4(6.8) in the non-GETA-group (p < 0.0001). Of the non-GETA group, 34(41.5%) patients were done under conscious sedation (CS) and 48(58.5%) under MAC. A favorable clinical outcome (mRS 0-2) was seen in 35.5% of the GETA-group versus 54.5% of the non-GETA-group (OR 0.4 95%CI: 0.25–0.83, p = 0.01). Mortality was observed in 40.2% of the GETA versus 21.5% of the non-GETA-group (OR 0.4 95%CI: 0.2–0.8, p = 0.006). The recanalization rate was not different across the groups. The intra-procedural pressure fluctuation defined as the difference between the maximum and minimum SBP was 60(±30) points in GETA and 47(±27) points in non-GETA-group (p = 0.02). For the GETA-group, the ΔSBP pre and post-induction was 11.5(±21) points for favorable and 20(±23) points for poor outcomes (p = 0.07). The time to groin puncture from angiography lab arrival time was significantly shorter, 36(±25) minutes in the non-GETA-group versus 53(±32) minutes in the GETA-group (p = 0.0006). Conclusion: GETA was associated with worse outcomes and higher mortality, however, GETA patients had also presented with worse deficits and by itself was not an independent predictor of outcome when NIHSS, age and recanalization were taken into account. A significantly higher BP fluctuation was seen in GETA versus non-GETA groups and a higher difference in pre and post-induction SBP portended a poor outcome amongst the GETA-group. Lastly the interval between arrival and groin puncture was significantly longer in GETA patients. At times GETA may be a necessity in sick patients, however, by strictly controlling BP and introducing measures to reduce delay in procedure start time (such as invasive BP monitoring through the femoral sheath), the "adverse" effect of GETA may be countered in endovascular stroke interventions. Disclosures: A. Rai: 2; C; Stryker Neurovascular, Codman Neuro. S. Boo: None. J. Domico: None. T. Roberts: None. J. Carpenter: None.